Respostas
respondido por:
1
Bom dia
log5(y - 4) - log5(y + 3) = 1
log5( (y - 4)/(y + 3) ) = log5(5)
(y - 4)/(y + 3) = 5
y - 4 = 5y + 15
4y = -19
y = -19/4
como y - 4 e y + 3 são negativos nâo existe solução
log5(y - 4) - log5(y + 3) = 1
log5( (y - 4)/(y + 3) ) = log5(5)
(y - 4)/(y + 3) = 5
y - 4 = 5y + 15
4y = -19
y = -19/4
como y - 4 e y + 3 são negativos nâo existe solução
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás